Estudio técnico económico de la incorporación del Green Sulf en la Empresa GydeMa - Madrigal Pérez, Arianna Esther (Universidad Central ‘‘Marta Abreu’’ de Las Villas. Facultad de Química y Farmacia. Departamento de Ingeniería Química, 2021)
The GydeMa Company has been developing a Research Project aimed at substituting solid sulfur for the generation of sulphurous water that the starch obtaining process requires. For this they have developed experimental studies that validate the use of Green Sulf - a product that works as a source of water-soluble sulfur - as an alternative product to the use of traditional sulfur. However, a technical study of how its introduction would be implemented in the production system has not been addressed. With this background, the present study evaluated alternatives for the introduction of the substitute product, taking into consideration that sulphurous water intervenes in different stages, with different magnitude and concentration. Four alternatives then resulted, including the current condition where Green Sulf does not intervene. Through the use of identification tools - aided with diagramming - the alternatives were examined, the differences were well defined and, in turn, the modifications to be made in each one. The different schemes were evaluated, making it possible to estimate the costs of the necessary investments and the differences in operating costs to facilitate comparison criteria. The need for investment is highlighted even when Green Sulf is not introduced due to the deterioration of the Sulfitation Plant, whose requirements were estimated. Other (qualitative) analysis criteria were used, such as the accessibility of each of the products and the environmental impact of their use in the process. The quantitative comparative analysis showed that the variant of using only Green Sulf promotes the lowest investment costs, in contrast, that of using solid sulfur absolutely offers the lowest operating costs. This last result may change if the drinking water used in such a condition is replaced by water from the recovery system. Qualitatively, the use of Green Sulf is unfavorable in terms of accessibility, but it far exceeds sulfur due to its reduced environmental impact when using them. The study offers technical and environmental elements that contribute to the Project that is being developed and for the directors of the GydeMa Company to make decisions.

La Empresa GydeMa viene desarrollando un Proyecto de Investigación encaminado a la sustitución del azufre sólido para la generación del agua sulfurosa que requiere el proceso obtención de almidón. Para ello han desarrollado estudios experimentales que validan la utilización del Green Sulf – un producto que funciona como fuente de azufre hidrosoluble – como producto alternativo al uso del azufre tradicional. Sin embargo, un estudio técnico de cómo se implementaría su introducción en el sistema productivo no ha sido abordado. Con estos antecedentes, el presente estudio evaluó alternativas para la introducción del producto sustituto, teniendo en consideración que el agua sulfurosa interviene en diferentes etapas, con diferente magnitud y concentración. Resultaron entonces cuatro alternativas, incluida la condición actual donde el Green Sulf no interviene. A través del uso de herramientas de identificación – auxiliadas con la diagramación – se examinaron las alternativas, quedado bien delimitadas las diferencias y a su vez las modificaciones a introducir en cada una. Los diferentes esquemas fueron evaluados, permitiendo estimar los costos de las inversiones necesarias y las diferencias en los costos operacionales para facilitar criterios de comparación. Se destaca la necesidad de inversión aun cuando no se introduzca el Green Sulf por el deterioro de la Planta de Sulfitación, cuyos requerimientos fueron estimados. Se manejaron otros criterios de análisis (cualitativos) tales como la accesibilidad a cada uno de los productos y el impacto ambiental por su utilización en el proceso. El análisis comparativo cuantitativamente arrojó que la variante de utilizar solo el Green Sulf, promueve los menores costos de inversión, en contraste, la de utilizar absolutamente el azufre sólido ofrece los menores costos de operación. Este último resultado puede cambiar si se sustituye el agua potable utilizada en tal condición, por agua del sistema de recuperación. Cualitativamente, la utilización del Green Sulf es defavorable en cuanto a la accesibilidad, pero supera con creces al azufre por su reducido impacto ambiental al utilizarlos. El estudio ofrece elementos técnicos y ambientales que contribuyen al Proyecto que se desarrolla y para que los directivos de la Empresa GydeMa tomen decisiones.
Keywords: Grano de Maíz; Almidón de Maíz; Obtención de Almidón; Proceso Tecnológico; Productos Auxiliares; Zea mays; Almidón